Local identity trhought global design - Rijo, Cátia (2014)
The purpose of this communication is to present a reflection on the importance of culture and heritage as transmitter of cultural identity, as the measure of an identity and image representing a community, and the contributions of design as a project that ensures the development of a construction of community identity. It discusses the importance of heritage and Culture as a differential factor for the construction of a local identity, since cultural diversity takes many forms through time and space. Culture constitutes the common heritage of humanity and should be recognized and affirmed for the benefit of present and future generations. Culture as transmitter of messages must be taken and understood as an essential element in the representation of a place. This article therefore intends to discuss the importance of local culture and to see how it can survive and project globally without losing its identity, and how design can project globally.